Evaluation of foot tissue meal of golden apple snail, Pomacea canaliculata (Gastropoda, Ampullariidae), as an ingredient in the gonad maturation diet of female shrimp Penaeus vannamei (Malacostraca, Penaeidae) broodstocks - Mary Jessa Bell B. Pagapulan; Rex Ferdinand M. Traifalgar; Sanny David P. Lumayno; Fredson H. Huervana; Dennis K. Gomez (Acta Ichthyologica et Piscatoria)
The Pacific white shrimp, Penaeus vannamei Boone, 1931, is one of the valuable globally-cultured species. However, its production in the Philippines has declined due to disease outbreaks. One essential approach to improve shrimp production is the use of domesticated broodstock to produce pathogen-free larvae, combined with well-formulated maturation diets, although fresh feeds can pose risks like disease transmission and water quality issues. Golden apple snail foot tissue meal (GASFTM) presents a cost-effective alternative protein source to squid meal, offering high protein content and the potential to improve aquaculture feed formulations. A 32-day feeding trial evaluated the effects of GASFTM on ovarian maturation of P. vannamei female broodstocks. Five isonitrogenous and isolipidic experimental diets containing increasing levels of GASFTM: control (0%), T1 (25%), T2 (50%), T3 (75%), and T4 (100%) were formulated. Polychaetes/squids and a basal control diet were used as the positive and negative controls, respectively. Each treatment with triplicate groups of 15 unilaterally eyestalk-ablated shrimp female broodstocks at early stages of ovarian development was fed with test diets. The ovarian development was tracked every four days. The results showed that the maximum ovary shadow ratios (OSR) as a measure of ovarian size was not different among the treatments. Ovarian maturation time (OMT) defined as the period between the initial and maximum OSR development indicate that the test diets with 50%, 75%, and 100% GASFTM were significantly shorter than those of the other treatments. The study also indicated that the test diets with 75% and 100% GASFTM inclusion were the most effective on P. vannamei ovarian maturation, followed by the test diet with 50% GASFTM inclusion. These findings suggest that GASFTM is a viable protein source for enhancing ovarian maturation and reproductive performance in P. vannamei broodstock.